Dismantling of Electric and Electronic Components from Waste Printed Circuit Boards by Hydrochloric Acid Leaching with Stannic Ions - Jung, M.; Yoo, Kyoungkeun; Alorro, Richard (Japan Institute of Metals and Materials, 2017)
A dismantling process for separating electric and electronic components (EECs) from printed circuit board (PCB) was developed by using hydrochloric acid (HCl) leaching with stannic ions (Sn⁴⁺). The use of HCl solution with Sn⁴⁺ ions dissolves tin (Sn)-alloy solder that holds EECs on bare board, which allows the EECs to be detached from PCB. The feasibility of the new dismantling process was investigated by examining the effects of temperature, initial Sn⁴⁺ concentration and agitation speed on the dismantling of PCB. The effect of agitation speed was negligible and the dismantling-completion time was reduced rapidly with increasing temperature and initial Sn⁴⁺ concentration. The dismantling of PCB was completed within 30 min under the leaching conditions; HCl concentration, 1 mol/L; initial Sn⁴⁺ concentration, 13,000 mg/L; temperature, 90℃; and agitation speed, 300 rpm. Each metal was enriched after dismantling process; e.g. the content of Ag increased from 0.016% in PCB to 3.118% in registor. It was expected that efficient PCB recycling process could be designed to recover metals from EECs with higher concentrated metals.